(untitled) (Лучшие интеллектуальные исследования, 2025)
Abstract: This study investigates the influence of emotional intelligence (EI) on the development of speaking skills among Uzbek learners of English as a Foreign Language (EFL). Emotional intelligence, which involves the ability to perceive, understand, manage, and use emotions effectively, has been recognized as a key factor in language learning success, especially in oral communication. Using a mixed-method approach, this research analyzes how components of EI correlate with learners’ speaking performance and confidence. Results suggest that higher EI levels contribute positively to learners’ ability to communicate fluently and manage anxiety during speaking tasks. The findings underscore the importance of incorporating emotional intelligence training into EFL teaching practices in Uzbekistan.